Evaluation of the Provision of Direct Observation of Procedural Skills (DOPS) on Physical Examination Skills and Water Seal Drainage (WSD) Treatment in Nursing Students - Susanti Susanti; Wisnu Sadhana; Surmiasih Surmiasih; Rika Damayanti; Rice Hernanda (GLOBAL HEALTH SCIENCE GROUP, 2025)
In improving student performance, clinical practice is needed, but before students practice in the field, mental preparation, knowledge and skills are needed, all of which we can find out by evaluating each student. Direct Observation of Procedural Skills (DOPS) is an evaluation method designed to address these gaps. The application of DOPS in health education in Indonesia is still relatively new and has not been widely integrated into the curriculum. However, the need for a more effective learning method is increasingly urgent, especially in the areas of procedural skills such as physical examination and WSD treatment. This study aims to determine the provision of the DOPS method to improve the skills of physical examination and WSD care in 4th semester nursing students at Aisyah Pringsewu University. This study used a quantitative approach with a quasy experimental design. This research design uses a One Group Pre-Post Test Without Control Group Design approach. The sample amounted to 32 respondents selected through the total sampling technique. Data were collected using the Standard Operating Procedure (SOP) with an independent t test. Results Show that the paired sample t-test above, known sig value. (2-tailed) is 0.001 <0.05, then Ho is rejected and Ha is accepted. So it can be concluded that there is a difference in the value of DOPS on physical examination skills and WSD Care. It is concluded that there is a significant difference between the control group and the intervention group before and after DOPS on physical examination skills and WSD.